Nepal’s Social Protection and Its Policy Alignment with Development Planning and SDGs: Emphasis on the 16th Plan - Phuyal, Ram Kumar (Journal of Social Protection, 2024)
This study explores the evolving landscape of Nepal’s social protection system, with a focus on its alignment with national development planning and the Sustainable Development Goals (SDGs), particularly within the framework of the 16th Periodic Plan (2081/82–2085/86). The primary objective of this paper is to assess how Nepal is institutionalizing social protection as a rights-based instrument for inclusive growth, economic resilience, and social justice—especially in the context of its upcoming graduation from Least Developed Country (LDC) status by 2026. The research employs a policy review and institutional analysis methodology, drawing on all the official planning documents, legal frameworks, and national strategies, including the Constitution of Nepal (2015), the Integrated National Social Protection Framework (INSPF) 2023, and the 16th Periodic Plan. Secondary sources and stakeholder insights from national and international organizations were also synthesized to provide a holistic picture of Nepal’s social protection reform journey. The findings reveal substantial progress in embedding social protection within the constitutional and planning architecture of Nepal. The 16th Periodic Plan represents a significant milestone in transitioning from fragmented welfare programmes to a coherent, life cycle-based, and inclusive social protection system. A key innovation is the operationalisation of the INSPF 2023, which integrates over 80 existing schemes under a unified governance and delivery framework and the introduction of the Integrated Information and Management System (IIMS). Nepal’s designation as a Pathfinder Country under the UN’s Global Accelerator on Jobs and Social Protection for Just Transitions has further reinforced its commitment to aligning domestic reforms with international goals, including climate resilience, decent work, and digital transformation. However, challenges remain, including fiscal constraints, institutional fragmentation, and gaps in coverage—especially for informal workers, women, youth, and migrants.